2014
DOI: 10.1080/03630242.2014.896445
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe Intimate Partner Violence and Violence-Related Injuries Among Women in India

Abstract: Relying on an ecological framework, we examined risk factors for severe physical intimate partner violence (IPV) and related injuries among a nationally representative sample of women (N = 67,226) in India. Data for this cross-sectional study were derived from the 2005-2006 India National Family Health Survey, a nationally representative household-based health surveillance system. Logistic regression analyses were used to generate the study findings. We found that factors related to severe physical IPV and inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 41 publications
7
75
2
1
Order By: Relevance
“…Previous studies have shown that socio-demographic factors, such as age, educational level, socio-economic status, and relationship/ marital status are associated with women's experiences of IPV (Kapiga et al 2017;Lacey et al 2016;Sabri et al 2014). However, the associations have not been consistent and there have been numerous factors influencing the risk of IPV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that socio-demographic factors, such as age, educational level, socio-economic status, and relationship/ marital status are associated with women's experiences of IPV (Kapiga et al 2017;Lacey et al 2016;Sabri et al 2014). However, the associations have not been consistent and there have been numerous factors influencing the risk of IPV.…”
Section: Discussionmentioning
confidence: 99%
“…Two separate multivariable logistic regression analyses were performed to explore factors associated with lifetime and pastyear IPV. All variables in the bivariate analysis were included in the multivariable analysis because all those independent variables have been demonstrated to be potential confounders through research literature search (Ali et al 2014;Capaldi et al 2012;Sabri et al 2014) and are important to be included in the final adjusted model regardless of whether they are statistically significantly related to the outcome. All independent variables were tested for multicollinearity and interactions with each other.…”
Section: Discussionmentioning
confidence: 99%
“…19 Similar results have been reported in India and South Africa. 20,21 This could be related to a high level of economic dependency by women on men, 16 which may make many women reluctant to report IPV. 22 In Uganda, a decrease in IPV has been associated with the empowerment of women, providing evidence to support the importance of education and delayed partnering for young women.…”
Section: Discussionmentioning
confidence: 99%
“…Çiftler arası şiddeti kabul etmede cinsiyet faktörü dışında madde kullanımı (Merghati-Khoei, Korte, Rimaz, Back, Brady ve Shamsalizadeh, 2014), ırk (Powers ve Kaukinen, 2012), güvensiz bağlanma (Craparo, Gori, Petruccelli, Cannella ve Simonelli, 2014), aşırı alkol tüketimi (Watkins, Maldonado ve Dilillo, 2014), erken çocukluk döneminde şiddet görme, aile içinde şiddete tanık olma (Yount ve ark., 2014;Sabri, Renner, Stockman, Mittal ve Decker, 2014), ilişkinin süresi (Thongpriwan, 2008) ve akılcı olmayan inançlara sahip olma (Vezina ve Hebert, 2007;Himelein, 1995;Harned, 2002) gibi başka faktörlerin de olduğu görülmektedir.…”
Section: Introductionunclassified